Rethinking Alternative Dispute Resolution Mechanisms in the Collective Bargaining Process in Nigeria - ADAMS, Adeola (Nigerian Journal of Peace, Development & Humanitarian Affairs, 2022)
This paper focuses primarily on conflict management process by appraising negotiation, mediation and arbitration as practiced by the industrial sector or trade unions in Nigeria today. First, the paper appraised the practice of collective bargaining process in Nigeria and argues that there is undue focus on the use of arbitration for settling industrial disputes, despite its obvious shortcomings. Second, the paper identifies some important values of collective bargaining shared with mediation. These core values include voluntariness, neutrality/impartiality, confidentiality, empowerment, mutual respect, democracy and interdependence. Thus, it is advocated that mediation, a more flexible process should be properly integrated and mainstreamed as a preferred tool of collective bargaining processes in trade disputes. The paper further suggests the adoption of hybrid processes such as MedArb or Arb-Med as the situation may dictate in the collective search for stability, peace and harmony in the workplace and the society at large. The data collected for this paper were derived mainly from secondary sources. Hence, the paper relied more on books, journals, monographs, conference/seminars papers and official documents of the Federal Government on National Employment Policy. Internet sources and other materials that are relevant to the theme of the paper were equally utilised. The collected data were subsequently reviewed thoroughly and content analysed.